NaIO4/KI/NaCl: a new reagent system for iodination of activated aromatics through in situ generation of iodine monochloride - Emmanuvel, Lourdusamy; Shukla, Ravi Kant; Sudalai, Arumugam; Gurunath, Suryavanshi; Sivaram, Swaminathan (Tetrahedron Letters, 2006)
A new reagent system consisting of NaIO4/KI/NaCl in aq AcOH has been found to be effective in iodinating a variety of activated aromatic substrates via in situ-generated iodine monochloride, to furnish iodoaromatics in excellent yields. This iodination procedure has been applied successfully for a cost-effective synthesis of 3,3'-diaminobenzidine, a key intermediate for preparing proton conducting membranes for fuel cell applications, with high yield and a purity of 99.7%. (c) 2006 Elsevier Ltd. All rights reserved.

NaIO4-mediated selective oxidation of alkylarenes and benzylic bromides/alcohols to carbonyl derivatives using water as solvent - Ali Shaikh, Tanveer Mahammad; Emmanuvel, Lourdusamy; Sudalai, Arumugam (Journal of Organic Chemistry, 2006)
A new transition-metal-free, sodium metaperiodate (NaIO4)-mediated direct oxidation of methylarenes and benzylic bromides to the corresponding aromatic carboxylic acids is described. Under the same reaction conditions, benzylic alcohols are selectively oxidized to afford the corresponding aldehydes in good yields without undergoing overoxidation. Unprecedentedly, oxidation of benzyl bromide, toluene, or benzyl alcohol with NaIO4 underwent nuclear bromination followed by oxidation to give 4-bromobenzoic acid in 60-79% yields.

NaIO4/LiBr-Mediated direct conversion of benzylic alcohols and aromatic aldehydes to aromatic esters - Shaikh, Tanveer Mohammad Ali; Emmanuvel, Lourdusamy; Sudalai, Arumugam (Synthetic Communications, 2007)
Aromatic aldehydes or benzylic alcohols are directly converted to the corresponding aromatic esters in high yields on treatment with methanol or ethanol mediated by sodium metaperiodate (NaIO4)/LiBr in an acidic medium.
Keywords: aromatic ester; benazaldehyde; Benzyl alcohol; Lithium bromide; Sodium metaperiodate

NaIO4-mediated asymmetric bromohydroxylation of alpha,beta-unsaturated carboxamides with high diastereoselectivity: a short route to (-)-cytoxazone and droxidopa - George, Shyla; Narina, Srinivasarao V.; Sudalai, Arumugam (Tetrahedron Letter, 2007)
The NaIO4-mediated asymmetric bromohydroxylation of alpha,beta-unsaturated carboxamides was achieved using lithium bromide as the bromine source under acidic conditions at rt to afford the corresponding chiral alpha-bromo-beta-hydroxy carboxamides. Excellent yields (77-90%) and diastereoselectivities (up to 10:1) along with exclusive control over regio- as well as anti-selectivity are the main features with a good scope of substrates. The method has successfully been applied in the enantioselective syntheses of two biologically important molecules, viz (-)-cytoxazone and L-threo-DOPS (droxidopa). (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: asymmetric bromohydroxylation; Carboxamide; cytoxazone; droxidopa; NaIO4

NaIO4-KI-NaN3 as a new reagent system for C-H functionalization in hydrocarbons - Chouthaiwale, Pandurang V.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2008)
The NaIO4-KI-NaN3 combination has been found to be an efficient, reliable, and inexpensive reagent system for mono- and 1,2-difunctionalization of hydrocarbons via C-H bond activation to afford vicinal azido- and acetoxy iodinations of cyclic hydrocarbons. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: azides; C-H activation; Iodination; NaIO4

NaIO4/LiBr-mediated aziridination of olefins using chloramine-T - Karabal, Pratibha U.; Chouthaiwale, Pandurang V.; Shaikh, Tanveer M.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2010)
A new milder protocol for aziridination of a variety of olefins has been described. The process employs catalytic amount of sodium metaperiodate (NaIO4) as an oxidant and LiBr and chloramine-T as the bromine and nitrogen sources, respectively. Interestingly, the formation of aziridine products in all the cases studied takes place presumably through a process of 1,2-aminobromination of alkenes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Aziridination; Chloramine-T; Lithium bromide; Olefin; Sodium metaperiodate

Novel synthesis and characterization of titanium superoxide and its application in organic oxidative processes - Reddy, R. Santhosh; Shaikh, Tanveer Mahamadali; Rawat, Varun; Karabal, Pratibha U.; Dewkar, Gajanan; Suryavanshi, Gurunath; Sudalai, Arumugam (Catalysis Surveys from Asia, 2010)
A novel, exceptionally stable titanium superoxide radical ion was prepared and its structure determined by FTIR, ESR, Raman spectroscopy, X-ray diffraction, thermogravimetric/differential thermal analysis and elemental analysis. This heterogeneous catalyst has been found to be effective for the selective oxidation of aromatic amines and phenols to the corresponding nitro aromatics and p-quinones, respectively. In addition, this non-toxic, inexpensive and reusable catalyst has also been used in aminobromination of olefins, which proceed to give the 1, 2-bromoaminated anti-Markovnikov product. A brief account of these results is summarized in this review.
Keywords: Amino Bromination; Anti-Markovnikov; heterogeneous catalyst; Oxidation; Titanium superoxide

NaIO4-NaN3-mediated diazidation of styrenes, alkenes, benzylic alcohols, and aryl ketones - Kamble, Dayanand A.; Karabal, Pratibha U.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Tetrahedron Letters, 2012)
Sodium periodate and sodium azide combination has been found to be an excellent reagent system suitable for the direct diazidation of styrenes, alkenes, benzylic alcohols, and aryl ketones to produce the corresponding vicinal and geminal diazides respectively in high yields under mild reaction conditions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: alkenes; Aryl ketones; Geminal diazides; Sodium periodate; Vicinal diazides

N-Heterocyclic carbene catalyzed esterification of aromatic aldehydes with alcohols under aerobic conditions - Kiran, I. N. Chaithanya; Lalwani, Komal G.; Sudalai, Arumugam (RSC Advances, 2013)
A simple, organocatalytic procedure for the direct oxidative esterification of a variety of aromatic aldehydes with alcohols has been described that affords the corresponding aromatic esters in high yields. The method employs N-heterocyclic carbenes as catalysts and molecular O-2 as an oxidant under ambient conditions.

N-Heterocyclic carbene catalyzed oxidative stannylation of aldehydes: a facile entry to organotin(IV) carboxylates - Reddi, Rambabu N.; Malekar, Pushpa V.; Sudalai, Arumugam (Tetrahedron Letters, 2013)
A simple protocol is described for the oxidative transformation of aldehydes to the corresponding organotin(IV) carboxylates in high yields (up to 90%) that utilizes atmospheric O-2 as the sole oxidant, N-heterocyclic carbene as catalyst (at 10 mol %), and tributyl tin chloride as stannylating agent. The uniqueness of the reaction lies in the direct conversion of aldehydes to the corresponding organotin(IV) carboxylates via stannylation of carboxylic acids, generated from the reaction of a Breslow intermediate with O-2. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carboxylic acid stannanes; N-Heterocyclic carbene; Oxidative stannylation; oxygen; Tributyltin chloride

N-Heterocyclic carbene catalyzed regioselective oxo-acyloxylation of alkenes with aromatic aldehydes: a high yield synthesis of alpha-acyloxy ketones and esters - Reddi, Rambabu N.; Malekar, Pushpa V.; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2013)
An N-heterocyclic carbene (NHC)-catalyzed reaction of alkenes with aromatic aldehydes providing for a high yield synthesis of alpha-acyloxy ketones and esters has been described. This unprecedented regioselective oxidative process employs NBS and Et3N in stoichiometric amounts and O-2 (1 atm) as an oxidant under ambient conditions in DMSO as a solvent.

N-Heterocyclic carbene catalyzed oxidative coupling of alkenes/alpha-bromoacetophenones with aldehydes: a facile entry to alpha,beta-epoxy ketones - Reddi, Rambabu N.; Prasad, Pragati K.; Sudalai, Arumugam (Angewandte Chemie-International Edition, 2015)
{A novel, N-heterocyclic carbene (NHC) catalyzed direct oxidative coupling of styrenes with aldehydes has been described for the synthesis of alpha,beta-epoxy ketones in good yields. This unprecedented regioselective oxidative coupling employs NBS/DBU/DMSO (DBU = 1,8-diazabicyclo [5.4. 0] undec-7-ene
Keywords: aldehydes; epoxidation; N-heterocyclic carbenes; Oxidation; synthetic methods

N-heterocyclic-carbene-catalyzed regioselective oxidative ring-opening of epoxides with aromatic aldehydes: a facile entry to alpha-acyloxyketones - Reddi, Rambabu N.; Gontala, Arjun; Prasad, Pragati K.; Sudalai, Arumugam (Asian Journal of Organic Chemistry, 2016)
A high-yielding synthesis of -acyloxyketones using a N-heterocyclic-carbene (NHC)-catalyzed, oxidative ring-opening of epoxides with aromatic aldehydes is described. This regioselective, oxidative process utilizes a N-bromosuccinimide (NBS)/DMSO combination as the oxidant system and Et3N as the base under mild reaction conditions.
Keywords: aldehydes; epoxides; halogen oxidants; N-heterocyclic carbenes; oxygen

Ni-Catalyzed dimerization and hydroperfluoroarylation of 1,3-dienes - Iwasaki, Takanori; Min, Xin; Fukuoka, Asuka; Zhu, Longzhi; Qiu, Renhua; Yang, Tao; Ehara, Masahiro; Sudalai, Arumugam; Kambe, Nobuaki (Journal of Organic Chemistry, 2018)